Multidisciplinaire sociale teams als cliëntgestuurd netwerk - Leni Beukema; Henk Spies (Journal of Social Intervention: Theory and Practice, 2006)
This article presents results from an evaluation research on social teams in the city of Leeuwarden. In these teams organisations for addicted people, mental health, social service, police, welfare and social work, try to co-ordinate their help and interventions with regard to multiproblem families. The authors present results at the individual level (citizens), the organisational level (participating organisations) and the level of local social policy. At the individual level it is remarkable that clients are often transferred from the ‘hard’ side to the ‘soft’ side of the teams, which is a positive thing from the point of view of prevention and safety. However, there is no systematic feedback and hardly any evaluation of the efficiency of the results. On the organisational level, participation in social teams seems to be too non-committal. This causes the teams to function as consultations rather than as an integral approach. On the level of social policy the status of the social teams is not yet clear. These teams could have an important role in tying together individual problems and problems in public spaces and neighbourhoods, as well as in tying together professional and informal networks. Especially with regard to the upcoming reforms in social support, this could be investigated further.